New strawberry cultivars and breeding activities in Brazil - Fagherazzi A.F.* (2017)
In Brazil, strawberry cultivation is a profitable agricultural activity, recording an expansion of the area under production year after year. However the lack of adapted cultivars and the absence of breeding programs affect Brazilian strawberry growers. The objective of this study is to show the progress of the activities concerning the introduction and the adaptability of new strawberry genotypes and the development of the breeding program of Agroveterinaries Sciences Center-University of the State of Santa Catarina (CAV-UDESC) in scientific cooperation with CREA-FRF, the Fruit Research Unit of Forlì, Italy.